Out-of-Pocket Expenditure of the Hospitalized Patients for Treatment of Liver Cirrhosis in a Tertiary Hospital (Journal of Preventive and Social Medicine, 2021)
Background: Out-of-pocket expenditure is the major financer for health care expenses in Bangladesh, causing financial burden on affected households. Chronic disease like liver cirrhosis requires long term treatment, exposing households to further economic stress, pushing them into a state where they fail to meet the necessary health expenses from their own household consumption and sacrifices basic necessities of living to pay for healthcare services. This study aims to estimate the OOP expenditure and resulting catastrophic health expenditure among hospitalized patients of liver cirrhosis.Methods: This was a cross-sectional study conducted among 42 diagnosed liver cirrhosis patients admitted at Bangabandhu Sheikh Mujib Medical University (BSMMU) under the department of hepatology and department of gastroenterology, aged 18 years and above. Convenient sampling technique was used and data were collected from the respondents using a semi-structured questionnaire through face-to-face interview during discharge from hospital.Results: Out of pocket expenditure for liver cirrhosis at BSMMU was BDT 24,898. Direct medical cost was BDT 21,202, direct non-medical cost was BDT 1,895 and indirect cost was BDT 1,801. Among the determinants of OOP healthcare expenditure, medicine and investigation costs were the major cost drivers, 36.91% and 44.13% of the total expenditure, respectively. OOP expenditure was found to be slightly higher among respondents from department of hepatology, than department of gastroenterology, BDT 21,834 and BDT 18,043 respectively, but this difference was not statistically significant. At 10% threshold level, 40.5% of the respondents were affected by Catastrophic Healthcare Expenditure (CHE). Nearly one-third (30.9%) of the respondents were facing distress financing due to OOP Expenditure.Conclusions: The high amount of OOP expenditure can be contributed mostly to the high cost of medicine and investigation. Making medicine readily available at an affordable price along with rational use of medication and investigation for diagnostic purpose can help reduce this financial burden on affected households.JOPSOM 2020; 39(2): 74-82